ANALISIS PERILAKU KONSUMEN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN MERK PRODUK - Ibra Oktariantara; Zidan Wahyu H; Ngabdul Mungiin (Universitas Haji Sumatera Utara, 2024)
In an era of increasingly fierce competition, a deep understanding of consumer behavior towards product brands has become very important for companies to maintain market share. This study aims to identify factors that influence consumer behavior, including brand image, product quality, and consumer preferences. In addition, this study also explores differences in consumer behavior across industries and cultural contexts. Using the meta-analysis method, this research combines results from various independent studies to gain a more comprehensive understanding of the effects of these variables. The results of this meta-analysis are expected to provide valuable insights for companies in formulating effective marketing strategies and increasing consumer loyalty to product brands.